Benefits and challenges of online project-based learning: Students and the lecturer's perceptions - Shofia Amin; Muthia Shahnaz (Universitas Negeri Yogyakarta, 2023)
Abstract: Project-based learning has been found to bring many benefits to learning. However, there have not been many studies that voice the challenges of using project-based learning in an online class. This study investigated the benefits and challenges of online project-based learning (PBL) according to students' and the lecturer’s perceptions. Using a qualitative case study design, the data were collected by distributing an open-ended questionnaire in Google forms to 45 students who joined the exchange students program of Merdeka Belajar Kampus Merdeka curriculum and doing a semi-structured interview with the lecturer. The exchange students took an Organizational Culture class at Universitas Jambi. This study found 17 benefits of using project-based learning in an online class, as well as 6 challenges that the students and the lecturers encountered during the class. This study suggested further instructors consider peer assessments, group reports, and additional consultation sessions to be included in online project-based learning classes.